A COMPARATIVE STUDY OF PUBLIC BUILDING MAINTENANCE STRATEGIES USING MULTI-CRITERIA METHODS BASED ON CONDITION AND FUNCTION - Widsri Lai Lai Palamba; Hans Dermawan; Jureine Queenmita Caerens Lolowang; Virginia Nathaniela; Nathanael; Christohodos Evert Willijhon Marlissa (Jurnal Pensil : Pendidikan Teknik Sipil, 2025)
Public buildings serve vital functions in supporting community services, yet they often experience quality degradation due to aging, weather conditions, and limited maintenance budgets. This study aims to conduct a comparative analysis of four public building maintenance case studies, each with different functions: administrative and educational dormitory buildings, traditional markets, churches, and elementary schools. The methods employed involve various Multi-Criteria Decision Making (MCDM) approaches. The comparative findings reveal that each method yields specific and adaptive outcomes tailored to the functional characteristics of the four public building types. The key findings indicate that maintenance planning based on priority and actual damage leads to more targeted outcomes, and highlight the need for a multidimensional approach in public building maintenance policy.